Establishment of a New Framework Administered Account for Selected Fund Activities. (Policy Papers; Policy Paper ;, 2009)
This paper proposes the approval of an instrument for the establishment of a new framework administered account to administer external financial resources for selected Fund activities (the 'SFA Instrument'). The SFA Instrument is designed to provide a more flexible platform through which the Fund may attract donor resources and meet the demand for its technical assistance (TA) and other activities.